Understanding heterogeneity: A mixed-method analysis to inform context-specific strategies for the inclusive scaling of improved bean varieties - Quintero, Katherine; Pérez, Yuliana; Taborda, Luis Alejandro; Pérez, Salomón; Reyes, Byron (2025)
This presentation analyzes the low adoption of improved bean varieties in Guatemala using a mixed-methods approach that combines surveys with 516 farmers and 12 semi-structured interviews with value chain actors. Through FAMD, hierarchical clustering, and thematic analysis, it identifies three farmer typologies that differ in age, market orientation, input use, and exchange networks, as well as other perspectives across the bean value chain. The findings show that there is no “average farmer,” and that institutional-level solutions are key to designing inclusive scaling strategies.